The Role of Intellectual Capital in Moderation of The Effect of Diversification on The Profitability and Technical Efficiency of Conventional Commercial Banks in Indonesia (Architecture Image Studies, 2026)
This study aims to examine the effect of income diversification and asset diversification on the profitability and technical efficiency of conventional commercial banks in Indonesia, as well as to investigate the moderating role of intellectual capital in these relationships. The research covers 68 conventional commercial banks in Indonesia during the 2013–2023 period. The analysis is conducted using the System Generalized Method of Moments (Sys-GMM) to address potential endogeneity and unobserved heterogeneity in dynamic panel data, while Data Envelopment Analysis (DEA) is applied to measure banks’ technical efficiency. The findings reveal that income diversification (IDI) has an insignificant effect on profitability but a negative and significant effect on technical efficiency, indicating that higher income diversification tends to reduce operational efficiency. Conversely, asset diversification (ADI) shows no significant influence on either profitability or efficiency. Regarding the components of intellectual capital, Structural Capital Efficiency (SCE) has a positive and significant impact on ROA and ROE, while Capital Employed Efficiency (CEE) exerts a positive and significant effect on technical efficiency. Meanwhile, Human Capital Efficiency (HCE) does not significantly affect any performance indicator. Moreover, Value Added Intellectual Capital (VAIC) has a positive and significant effect on both ROA and ROE, underscoring the role of intellectual capital in enhancing banks’ profitability. In terms of moderation effects, SCE strengthens the relationship between income diversification and profitability (ROA), while HCE and CEE weaken the effect of asset diversification on profitability (ROE). These results suggest that the moderating role of intellectual capital varies depending on the type of diversification and the performance dimension examined. Overall, this study contributes to the banking literature by highlighting how intellectual capital can either reinforce or diminish the impact of diversification strategies on bank performance, providing both theoretical insights and practical implications for regulators and bank management in formulating strategies to enhance competitiveness and efficiency in the Indonesian banking sector.